2004
DOI: 10.1002/jcu.20027
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of transperineal and transvaginal sonography in predicting preterm delivery

Abstract: When the cervix is well visualized, TPUS can predict preterm delivery as accurately as TVUS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 24 publications
2
17
0
1
Order By: Relevance
“…8 Iams et al and Berghella et al concluded cervical length is inversely related to the risk of preterm birth in asymptomatic women. 1,9 In present study increment in cervical widths are noted in both patients who undergone term delivery and those having preterm delivery (except at 30wk) on follow up. However no significant difference is noted between both groups by TA and TV Us.…”
Section: Discussionsupporting
confidence: 56%
“…8 Iams et al and Berghella et al concluded cervical length is inversely related to the risk of preterm birth in asymptomatic women. 1,9 In present study increment in cervical widths are noted in both patients who undergone term delivery and those having preterm delivery (except at 30wk) on follow up. However no significant difference is noted between both groups by TA and TV Us.…”
Section: Discussionsupporting
confidence: 56%
“…On TPU, the most important technical problem is the possible interference of adjacent bowel gas with cervical image 33 . The elevated lithotomy position helps to alleviate rectal gas overlying the external os.…”
Section: Introductionmentioning
confidence: 99%
“…TPU has been shown to have a sensitivity of 77% in predicting PTB with a false‐positive rate of 17% and a relative risk of 4.5 at the 32.5 mm cut off value 33 . In cases where a PROM is suspected or the patient declines the TV approach the TPU is useful.…”
Section: Introductionmentioning
confidence: 99%
“…This method is reproducible, safe and more accurate than digital examination or abdominal or transperineal ultrasound [7,14,18,19] . Transvaginal ultrasound of the cervix also enables early detection of a shortening of the supravaginal portion of the cervix which is not amenable to clinical examination [20,21] .…”
Section: Discussionmentioning
confidence: 99%